EKSPRESI MAKSIM PRINSIP SOPAN SANTUN DIALOG FILM DIBAWAH LINDUNGAN KA’BAH DAN IMPLIKASINYA - Siti Komsiyah; Wini Tarmini; Nurlaksana Eko Rusminto (FKIP Universitas Lampung, 2013)
The problems discussed in this research are the expression of maxims of politeness principle in the dialogue on Di Bawah Lindungan Ka’bah movie By Hanny Saputra and its implications on learning Indonesian language in high School. This study aims to describe the expression of maxims of politeness principle in the dialogue on Di Bawah Lindungan Ka’bah movie By Hanny Saputra and its implications on learning Indonesian language in high School. Research method used in this research is descriptive qualitative. Data source in this study is Di Bawah Lindungan Ka’bah movie By Hanny Saputra, published by MD Pictures with duration 1 hour 53 minutes. Based on the result of research that the sixth maxims of politeness principle can be used in expression. They are the wisdom maxim, generosity maxim, commendatory maxim, modesty maxim, agreement maxim, and sympathy maxim. The expression of maxims of politeness principle which-most frequenty appearcs is modesty maxim and which less appercs is wisdom maxim. The result of this research can be implied with Indonesian Language learning in high school as learning materials particularly in listening and speaking skills.Key words: expression, maxims of politeness principle, movie, implications.